Akt regulates neurite growth by phosphorylation-dependent inhibition of radixin proteasomal degradation - Eun-Ju Jin (Nature Portfolio, 2018)
Abstract Neurite growth is controlled by a complex molecular signaling network that regulates filamentous actin (F-actin) dynamics at the growth cone. The evolutionarily conserved ezrin, radixin, and moesin family of proteins tether F-actin to the cell membrane when phosphorylated at a conserved threonine residue and modulate neurite outgrowth. Here we show that Akt binds to and phosphorylates a threonine 573 residue on radixin. Akt-mediated phosphorylation protects radixin from ubiquitin-dependent proteasomal degradation, thereby enhancing radixin protein stability, which permits proper neurite outgrowth and growth cone formation. Conversely, the inhibition of Akt kinase or disruption of Akt-dependent phosphorylation reduces the binding affinity of radixin to F-actin as well as lowers radixin protein levels, resulting in decreased neurite outgrowth and growth cone formation. Our findings suggest that Akt signaling regulates neurite outgrowth by stabilizing radixin interactions with F-actin, thus facilitating local F-actin dynamics.